TINJAUAN YURIDIS TERHADAP SURAT PERJANJIAN SEWA MENYEWA RUMAH JABATAN WAKIL MENTERI DALAM NEGERI BERDASARKAN KETENTUAN KUHPERDATA - Rahmayanti, Anita Sri; Indiraharti, Indiraharti (Tribuere, 2023)
This research is motivated by a legal event about leasing between Fauzan Hasan, S.STP., M.Si, Commitment Making Officer of the General Bureau of the Secretariat General of Kemdagri with Parwati Surjaudaja who agreed to lease by making a written agreement. In terms of law, the above is in accordance with the law. Making a lease agreement in writing will facilitate dispute resolution in the event of unwanted things, for example, one of the parties defaults or does not perform its obligations as it should. The subject matter of this research, how are the provisions on halal causa in the law of house lease agreements and whether the lease agreement of the Deputy Minister of Home Affairs Office House has fulfilled halal causa. The type of research uses descriptive analytical method and the approach is normative juridical, namely examining data logically based on literature studies which are secondary materials in the field of law. The data is analyzed qualitatively and the conclusion is drawn deductively.  Based on the results of the research, it can be concluded that the written lease agreement mentioned above is in accordance with the provisions of civil law and legal aspects governing the validity of an agreement and has legal force and fulfills the requirements of a lawful cause. . "A Halal Cause" means that the agreement made does not conflict with the law, public order and decency. The object of the agreement, a house located at Jalan Maluku No. 29 RT 006/RW 005 Gondangdia Menteng, Central Jakarta